Investigation of Texts and Images in Life Science Textbooks in Terms of Values - Talip Öztürk; Zeynep Sude Özkan (Anı Publishing, 2018)
In this research, it was aimed to examine of primary school 3rd grade Life Science textbooks' texts and visuals of a private publishing firm, which was used in 2016-2017 education year, in terms of value education. Qualitative research methods in the research were carried out in the analytical research design and the data were collected through the documents consisting of the textbooks. In the analysis of the data, content analysis method was taken as basis. A "Value Inspection Form" was prepared by the researcher in accordance with the definitions of Turkish National Education. The situation of the 20 values in textbooks which are aimed to be given to the students in the 3rd grade life science curriculum was investigated by using the prepared "Value Assesent Form". First, the value expressions in the texts are determined. Then, those carrying the aim of value education from visual expressions have been identified. These data was obtained from text and pictures then coded and classified. The analysis process was done by using NVivo 10 software program. According to the results of the study, it was seen that the most value in the textbook was "Love" and the least value was "Hospitality". In the texts and images of the Life Science lesson books, it is necessary to make arrangements with more emphasis on the values that students find little such as "patience", "scientificness", "love of nature", "aesthetics" and "hospitality".